2022
DOI: 10.21511/im.18(4).2022.04
|View full text |Cite
|
Sign up to set email alerts
|

Does brand love strictly increase purchase intention? The case of Linio

Abstract: Given that feelings toward a brand allow for a mutually beneficial relationship, it is easy to assume that they are closely related to the customer’s willingness to buy as if they increase or decrease probably in the same proportion. Consequently, this study aims to observe the attractiveness of the Linio brand, one of Latin America’s most important e-commerce platforms, on the part of its consumers in northern Peru. The paper is quantitative, correlational, cross-sectional, and non-experimental; a probabilist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Therefore, Melović (2020) expressed that social networks are the digital marketing media that companies use regularly, which encompasses that digital marketing, social media marketing, creative content and mobile advertising work as trends to develop the number of customers. Also, social and digital networks contribute to achieving business objectives at low cost, which makes them an essential factor in digital marketing plans (Dwivedi, 2020;Rocha-Vallejos et al, 2022;Riofrio-Carbajal et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, Melović (2020) expressed that social networks are the digital marketing media that companies use regularly, which encompasses that digital marketing, social media marketing, creative content and mobile advertising work as trends to develop the number of customers. Also, social and digital networks contribute to achieving business objectives at low cost, which makes them an essential factor in digital marketing plans (Dwivedi, 2020;Rocha-Vallejos et al, 2022;Riofrio-Carbajal et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Customer loyalty is the key for any business to grow, since the relationship with the customer is very satisfactory; Since relationship marketing appeared, it has consisted of attracting and maintaining a long-term relationship with the customer, being a competitive sale and a more oriented conception for the market that nowadays is always in constant change (Alcivar Acosta, 2018;Rocha-Vallejos et al, 2022). Relationship marketing is defined by 3 dimensions which are endomarketing, a very important technique to motivate the company's employees, customer retention through good service, keeping them satisfied and communication to have a better customercompany relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The same ones who have applied their study to various areas, sectors and populations, such as: medicine (Ebert et al, 2002), business (Suryani et al, 2022), social sciences (Mustafa et al, 2022), psychology (Jakubiec et al, 2014), economics (Peng et al, 2022), humanities (Raja et al, 2020), among others. When discerning scientific dissemination by country, it has been found that the studies carried out in the Peruvian population (Caycho-Rodríguez et al, 2020;Pino et al, 2020;Chavez-Espinoza et al, 2022;Rocha-Vallejos et al, 2022;Alipio et al, 2023) are very limited, that is, there is very little scientific literature that can provide support and guidance for future studies, and that can provide relevant information to develop communication strategies, health promotion, improving wellbeing and general health in the Peruvian context. Given the prevalence of diseases and the current situation of occupational health, this research aims to fill the knowledge gap and provide a valuable contribution to the academic community and professionals of the sectors involved.…”
Section: Introductionmentioning
confidence: 99%